2010
DOI: 10.1021/nn901873t
|View full text |Cite
|
Sign up to set email alerts
|

Stereocomplexed Poly(lactic acid)−Poly(ethylene glycol) Nanoparticles with Dual-Emissive Boron Dyes for Tumor Accumulation

Abstract: Responsive biomaterials play important roles in imaging, diagnostics, and therapeutics. Polymeric nanoparticles (NPs) containing hydrophobic and hydrophilic segments are one class of biomaterial utilized for these purposes. The incorporation of luminescent molecules into NPs adds optical imaging and sensing capability to these vectors. Here we report on the synthesis of dual-emissive, pegylated NPs with "stealth"-like properties, delivered intravenously (IV), for the study of tumor accumulation. The NPs were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 53 publications
1
55
0
Order By: Relevance
“…For this reason, the use of intravenous administration has also been considered and we have developed a PEGylated nanoparticle formulation that was found to accumulate near the tumor vasculature using confocal imaging. 28 In conclusion, we have demonstrated and validated techniques by which vascular and tissue oxygenation can be imaged at high spatial and temporal resolution, enabling a detailed understanding of the tumor microenvironment and its influence on tumor gene expression. All these techniques are implemented using a simple modification to a standard fluorescent microscope, enabling a wide range of potential applications.…”
Section: Figmentioning
confidence: 85%
“…For this reason, the use of intravenous administration has also been considered and we have developed a PEGylated nanoparticle formulation that was found to accumulate near the tumor vasculature using confocal imaging. 28 In conclusion, we have demonstrated and validated techniques by which vascular and tissue oxygenation can be imaged at high spatial and temporal resolution, enabling a detailed understanding of the tumor microenvironment and its influence on tumor gene expression. All these techniques are implemented using a simple modification to a standard fluorescent microscope, enabling a wide range of potential applications.…”
Section: Figmentioning
confidence: 85%
“…Specifically, with BF 2 dbmPLA (dbm = dibenzoylmethane) 10,11,1519 and its halogenated, heavy atom congener, BF 2 dbm(I)PLA, 14 we demonstrated that emission wavelengths, relative F/P intensities, and oxygen sensitivities are tunable with heavy atom substitution and polymer molecular weight 11,15 and that these materials can be exploited for cellular, 14,15 tissue, and in vivo imaging studies (e.g., tumor hypoxia 14,18 ).…”
Section: Introductionmentioning
confidence: 88%
“…It is multi-emissive, exhibiting both short-lived fluorescence (F) and long-lived fluorescence (P) after one-or two-photon excitation. Recently, dual-emissive pegylated BNPs have been fabricated, and they have been shown to have long-circulating, ''stealth''-like properties for studying tumor accumulation and hypoxia imaging in preclinical studies (117).…”
Section: Non-invasive Hypoxia Imagingmentioning
confidence: 99%